Flipped classroom model of mathematics learning outcomes - I Susanti; E C Asih; B A Priatna (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The aim of this research was to investigate the flipped classroom model. Students experienced difficulties in learning mathematics. Thus, learning innovation is needed to help them maximize their learning and practice in solving maths problems. The learning model dicussed in this research was the flipped classroom learning model. This model is the reversed learning model and considered suitable for mathematics learning.